Desain Mitigasi Risiko Rantai Pasok Darah Menggunakan Pendekatan Baru - Heryanto, Rainisa Maini; Liputra, David Try; Arisandhy, Vivi; Amalina, Ninda Nurseha (Universitas Katolik Parahyangan, 2024)
Blood is an essential component for body and plays critical role in human survival. Hospital blood banks (HBB) are responsible for ensuring availability and safety of blood in particular area. Risks that could arise in blood supply chain at HBB need to receive full attention, especially in the event of an outbreak or disaster. This attention is necessary to ensure smooth flow of activities, information, products, and finances. The primary objective of this research is to develop risk mitigation design for the blood supply chain. This research focuses on case study at HBB in Bandung City with specific focus on packaged red blood cells. The new approach used in this research involves initiating process by collecting potential risks, which are then defined and classified within the supply chain operations reference (SCOR) model. Subsequently, questionnaires were distributed to gather input for calculating weights using the analytical hierarchy process (AHP). Following step involves identifying root cause of these risk through fault tree analysis (FTA) and determining the most influential risk causes using failure mode effect and analysis (FMEA). Final phase entails designing strategies for mitigating risks in blood supply chain. This research aims to assist HBB facilities in prioritizing risks for treatment and implementing strategies to minimize these risks within their respective areas. According to AHP results, risk with the highest weight (0.173) is unavailability of blood stock at Indonesian Red Cross due to a shortage of donors. This risk can be mitigated by incorporating blood donation activities in agencies and HBB. The new approach in the research could provide more detailed mapping of blood supply chain risks.